Bacterial Community Structure of HA-A/A-MCO Sludge Reduction Process - Zuo, Ning; Ji, Fang-Ying (Asian Journal of Chemistry, 2013)
An advanced process combining sludge reduction and phosphorous and nitrogen removal is developed, for short, HA-A/A-MCO process. The bacterial community structure of the process is analyzed by PCR-DGGE fingerprinting. The results indicates that the microbial flora showed the distinction of highly diversity in anaerobic tank, anoxic tank and multistep continuous oxic tank of the HA-A/A-MCO process and each tank has its own diversified and stable dominant microorganisms, as in the center of the maintance of a good phosphorus removal performance and leptospires sp. undertakes the function of organic matter removal and helps to keep a good capability to remove organic matter. Bacillus sp. and lampropedia sp. and other so the co-activation of such preponderant bacterial community promotes the system to exert favourable and consistent function of phosphorous and nitrogen removal and sludge reduction. The results of species identification shows that Acinetobacter sp. lies bacterium can propagate in bacterial culture area, which will disappear because of predation of higher living organisms in protozoa growing area and metazoan growing area. Such predation can promote high effective sludge reduction of HA-A/A-MCO process.